Designing Adaptive Virtual Worlds - Maher, Mary Lou (De Gruyter, 2014)
Designing adaptive virtual worlds takes the design of places for education, entertainment, online communities, business, and cultural activities in 3D virtual worlds to a new level. The place metaphor provides a rich source of styles and examples for designing in 3D virtual worlds. This book is one of the first design books in the field showing how those styles can be captured in a design grammar so that unique places can be created through computational agents responding to the changing needs of the people in the virtual world. Applying the techniques introduced in this book has immediate implications on the design of games and functional places in existing virtual world platforms such as Second Life, OpenSim and Active Worlds as well as future virtual worlds in which the boundaries between digital and physical environments blur.